Development of a structural equation model for sustainable construction practices in Nigeria - H. C. O. Unegbu; D. S. Yawas; B. Dan-asabe; A. A. Alabi (Discover Civil Engineering)
Abstract This study develops a sustainability model to promote sustainable construction practices in Nigeria. Utilizing Structural Equation Modeling (SEM), the research investigates the interrelationships among several independent latent constructs—organizational culture, government policies, financial implications, stakeholder processes, and technology availability—and their effects on sustainability outcomes. Data were collected through a survey questionnaire from 248 respondents across ten selected construction companies in Nigeria, analyzed using the SIMPLEX Project in LISREL. The SEM highlights the significant influence of government policies (GPR) on sustainability outcomes, particularly regarding organizational culture (OC), availability of technology and expertise (ATE), financial implications (SI), and stakeholder processes (SP). This is evidenced by substantial path coefficients: GPR → OC (β = 0.45), GPR → ATE (β = 0.58), GPR → FI (β = 0.75), GPR → SP (β = 0.49), all p < 0.01. Additionally, organizational culture significantly impacts sustainability dimensions, with OC → ATE (β = 0.55), OC → SP (β = 0.63), and OC → FI (β = 0.76), all p < 0.01. Government policies exhibited the most considerable influence across three sustainability domains: environmental sustainability (ENS), social sustainability (SS), and economic sustainability (ES), as indicated by GPR → ENS (β = 0.87), GPR → SS (β = 0.68), and GPR → ES (β = 0.72), all p < 0.05. The derived mathematical model for Sustainable Construction Practices (SCP) is SCP = 0.01 + 0.5x + 0.3y + 0.2z, where x, y, and z represent environmental, social, and economic sustainability, respectively. The findings underscore the interconnected nature of these dimensions, offering vital recommendations for policymakers and industry stakeholders to foster sustainable practices in Nigeria's construction sector.